Computed tomography‐defined body composition as prognostic markers for unfavourable outcomes and in‐hospital mortality in coronavirus disease 2019. Issue 1 (12th January 2022) - Meyer, Hans‐Jonas; Wienke, Andreas; Surov, Alexey
Abstract: Background: Low skeletal muscle mass (LSMM) and visceral fat areas can be assessed by cross‐sectional images. These parameters are associated with several clinically relevant factors in various disorders with predictive and prognostic implications. Our aim was to establish the effect of computed tomography (CT)‐defined LSMM and fat areas on unfavourable outcomes and in‐hospital mortality in coronavirus disease 2019 (COVID‐19) patients based on a large patient sample. Methods: MEDLINE library, Cochrane, and Scopus databases were screened for the associations between CT‐defined LSMM as well as fat areas and in‐hospital mortality in COVID‐19 patients up to September 2021. In total, six studies were suitable for the analysis and included into the present analysis. Results: The included studies comprised 1059 patients, 591 men (55.8%) and 468 women (44.2%), with a mean age of 60.1 years ranging from 48 to 66 years. The pooled prevalence of LSMM was 33.6%. The pooled odds ratio for the effect of LSMM on in‐hospital mortality in univariate analysis was 5.84 [95% confidence interval (CI) 1.07–31.83]. It was 2.73 (95% CI 0.54–13.70) in multivariate analysis. The pooled odds ratio of high visceral fat area on unfavourable outcome in univariate analysis was 2.65 (95% CI 1.57–4.47). Conclusions: Computed tomography‐defined LSMM and high visceral fat area have a relevant association with in‐hospital mortality in COVID‐19 patients and should be included as relevant prognostic biomarkers into clinical routine.